Changes in overactive bladder symptoms after sodium glucose cotransporter‐2 inhibitor administration to patients with type 2 diabetes. (6th April 2018) - Shikuma, Junpei; Ito, Rokuro; Sasaki‐Shima, Junko; Teshima, Akiko; Hara, Kazuo; Takahashi, Tomono; Sakai, Hiroyuki; Miwa, Takashi; Kanazawa, Akira; Odawara, Masato
Abstract: The aim of this study was to investigate the changes in overactive bladder symptoms after selective sodium glucose cotransporter‐2 (SGLT2) inhibitor administration to patients with type 2 diabetes. Outpatients with type 2 diabetes who consented to participate in this study between September 2014 and August 2015 were included. Overactive bladder assessments were conducted before and one month after SGLT2 inhibitor administration using the Overactive Bladder Symptom Score (OABSS). Fifty‐eight patients were enrolled. OABSSs indicated that 17.2% of the subjects had overactive bladder. Comparison of OABSSs before and after SGLT2 inhibitor administration indicated that Q1 (daytime frequency) and total scores increased significantly. Post‐hoc analysis indicated that in the group without overactive bladder according to pre‐administration OABSSs, statistically significant increases were observed for Q1 (daytime frequency), Q3 (urgency), and total scores. Conversely, in the group with overactive bladder, there were no significant differences. The mean score for Q1 (daytime frequency) increased, whereas that for Q3 (urgency) decreased. It was concluded that SGLT2 inhibitor administration to patients with type 2 diabetes, but without overactive bladder, caused significant increases in daytime frequency but not in night‐time frequency. However, in patients with overactive bladder prior to SGLT2 inhibitor administration, blood glucose control was possible without worsening overactive bladder. Copyright © 2018 John Wiley & Sons.